Factors Influencing COVID-19 Vaccination Intentions Among College Students: A Cross-Sectional Study in India - Jain, Lovely; Vij, Jatina; Satapathy, Prakasini; Chakrapani, Venkatesan; Patro, Binod; Kar, Sitanshu Sekhar; Singh, Ritesh; Pala, Star; Sankhe, Lalit; Modi, Bhavesh; Bali, Surya; Rustagi, Neeti; et al. (Frontiers in Public Health, 2021)
Background: Students act as messengers in delivering effective messages for better uptake of health-promoting behavior. Understanding their knowledge about coronavirus disease 2019 (COVID-19), intentions to use the COVID-19 vaccine, and its associated factors will help develop promising strategies in vaccine promotion concerning the current COVID-19 pandemic. Methods: A cross-sectional online survey was carried out among students in the healthcare and non-healthcare sectors to assess their intentions to get vaccinated against the COVID-19. A non-probability snowball sampling technique was used to recruit study participants (N = 655) through social media platforms and emails. Study participants were recruited across the country, including six major geographical regions (Eastern, Western, Northern, Southern, North-east, and Central) in India between November 2020 and January 2021 before the introduction of the COVID-19 vaccine. Descriptive statistics were used to present the sociodemographic, and vaccine-related behaviors of the study participants. Key determinants that likely predict vaccine acceptance among students were modeled using logistic regression analysis. For each analysis, p < 0.05 was considered significant. Results: A total of 655 students were recruited, 323 from healthcare and 332 from non-healthcare sectors, to assess their intentions to receive the COVID-19 vaccine. Of the 655 students, 63.8% expressed intentions to receive the COVID-19 vaccine. The acceptance was higher among non-healthcare students (54.07 vs. 45.93%). At the time of the study, 27.8% of the students indicated that they had been exposed to a confirmed COVID-19 patient. A vast majority (93.4%) of the students knew about the COVID-19 virus, and most (89.3%) of them were aware of the development of a COVID-19 vaccine. The history of vaccine hesitancy was found to be low (17.1%). Only one-third (33.4%) of the students showed concern about contracting COVID-19. Trust in the healthcare system [adjusted odds ratio (aOR): 4.13; (95% CI: 2.83–6.04), p < 0.00] and trust in domestic vaccines [aOR: 1.46; (95% CI: 1.02–2.08), p < 0.05] emerged as the significant predictors of student's intention to get vaccinated. Higher acceptance for vaccine was observed among students in the non-healthcare [aOR: 1.982; 95% CI: 1.334–2.946, p < 0.00]. Conclusion: This study shows that the Indian college students had relatively high levels of positive intentions to receive COVID-19 vaccines, although about one-third were not sure or unwilling to receive the vaccine, highlighting possible vaccine hesitancy. Informational campaigns and other strategies to address vaccine hesitancy are needed to promote uptake of COVID-19 vaccines.